2016
DOI: 10.1098/rsta.2015.0279
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical analysis of the degradation of fibre-reinforced polymers under the presence of void imperfections

Abstract: The subject of this work is the investigation of the influence of voids on the mechanical properties of fibre-reinforced polymers (FRPs) under compression loading. To specify the damage accumulation of FRPs in the presence of voids, the complex threedimensional structure of the composite including voids was analysed and a reduced mechanical model composite was derived. The hierarchical analysis of the model composite on a micro-scale level implies the description of the stress and strain behaviour of the matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Therefore, to estimate the compressive strength, the critical number of affected fibers by voids needs to be determined through a probabilistic approach, in addition to the void content. Although in contrast to the approach presented by Hapke et al, 270 the methodology investigated by Liebig et al 218,227,242 shows information also about failure initiation, it is still not representative of the compressive failure in real composites. This can be attributed to the lower fiber volume fraction, larger fiber diameter ($70 mm), and larger size of voids (up to 3500 mm length and 800 mm height) compared with typical composites.…”
Section: Compressive Propertiesmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, to estimate the compressive strength, the critical number of affected fibers by voids needs to be determined through a probabilistic approach, in addition to the void content. Although in contrast to the approach presented by Hapke et al, 270 the methodology investigated by Liebig et al 218,227,242 shows information also about failure initiation, it is still not representative of the compressive failure in real composites. This can be attributed to the lower fiber volume fraction, larger fiber diameter ($70 mm), and larger size of voids (up to 3500 mm length and 800 mm height) compared with typical composites.…”
Section: Compressive Propertiesmentioning
confidence: 84%
“…In a further study, 242 the authors showed that DIC indicates also minimum and maximum strains in the summit and in the middle of the void, respectively. The high strain alongside the void was linked to the fiber deflection into the void, which accompanies the non-linear deformation of the matrix.…”
Section: Compressive Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…Initiation of kink-bands is facilitated at defects, e.g., voids [ 9 , 10 ] or local fibre misalignment [ 11 ]. Despite these flaws, the laminate properties and stacking sequence play an important role in damage initiation and propagation and the resulting mechanical properties under compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical model of Argon [18] that assumes rigid-plastic microbuckling and the extension from Budiansky [19,20,21], which considers elastic-plastic microbuckling, describe the initiation and propagation of a kink-band with an orientation angle β, the kink-band width, and the inclination angle of the fibres. Initiation of fibre microbuckling and a kink-band is facilitated at defects, e.g., local fibre misalignment [22,23,24,25] or voids [26,27] and can be described for the latter case with an analytical model [28]. It was shown by Bazhenov et al [29] that the fibre diameter is relevant for compressive strength, especially if flaws such as voids are present.…”
Section: Introductionmentioning
confidence: 99%